Platelet lysate 3D scaffold supports mesenchymal stem cell chondrogenesis: An improved approach in cartilage tissue engineering - Moroz, Andrei[UNESP]; Bittencourt, Renata Aparecida Camargo; Almeida, Renan Padron [UNESP]; Felisbino, Sérgio Luis [UNESP]; Deffune, Elenice [UNESP] (Taylor & Francis, 2013)
Articular lesions are still a major challenge in orthopedics because of cartilage's poor healing properties. A major improvement in therapeutics was the development of autologous chondrocytes implantation (ACI), a biotechnology-derived technique that delivers healthy autologous chondrocytes after in vitro expansion. To obtain cartilage-like tissue, 3D scaffolds are essential to maintain chondrocyte differentiated status. Currently, bioactive 3D scaffolds are promising as they can deliver growth factors, cytokines, and hormones to the cells, giving them a boost to attach, proliferate, induce protein synthesis, and differentiate. Using mesenchymal stem cells (MSCs) differentiated into chondrocytes, one can avoid cartilage harvesting. Thus, we investigated the potential use of a platelet-lysate-based 3D bioactive scaffold to support chondrogenic differentiation and maintenance of MSCs. The MSCs from adult rabbit bone marrow (n=5) were cultivated and characterized using three antibodies by flow cytometry. MSCs (1×105) were than encapsulated inside 60μl of a rabbit platelet-lysate clot scaffold and maintained in Dulbecco's Modified Eagle Medium Nutrient Mixture F-12 supplemented with chondrogenic inductors. After 21 days, the MSCs-seeded scaffolds were processed for histological analysis and stained with toluidine blue. This scaffold was able to maintain round-shaped cells, typical chondrocyte metachromatic extracellular matrix deposition, and isogenous group formation. Cells accumulated inside lacunae and cytoplasm lipid droplets were other observed typical chondrocyte features. In conclusion, the usage of a platelet-lysate bioactive scaffold, associated with a suitable chondrogenic culture medium, supports MSCs chondrogenesis. As such, it offers an alternative tool for cartilage engineering research and ACI. © 2013 Informa UK Ltd.
Keywords: 3D cell culture; Cartilage; Chondrogenesis; Extracellular matrix; Mesenchymal stem cells; Platelet gel; Platelet-rich plasma; Scaffolds; tissue scaffold; animal cell; animal tissue; bone marrow culture; cartilage; cartilage cell; cell differentiation; cell lysate; cell structure; cellular distribution; chondrogenesis; controlled study; culture medium; extracellular matrix; flow cytometry; histology; in vitro study; mesenchymal stem cell; microencapsulation; nonhuman; phase contrast microscopy; priority journal; rabbit; thrombocyte; thrombocyte count; tissue engineering; Animals; Blood Platelets; Cell Culture Techniques; Mesenchymal Stromal Cells; Rabbits; Tissue Engineering; Tissue Scaffolds